The WIfI classification as a prognostication of lower extremity artery sclerosis development and benefits resulting from therapy implementation - Mościcka, Paulina; Szewczyk, Maria T.; Cwajda-Białasik, Justyna; Jawień, Arkadiusz (Pielęgniarstwo Chirurgiczne i Angiologiczne/Surgical and Vascular Nursing, 2018)
Critical lower limb ischaemia concerns about 1% to 3% of diseased people with chronic lower limb ischaemia. The resulting clinical state and a possible attempted prediction of effectiveness within lower limb sclerosis and coexisting diabetes patients is usually limited. This is because of diabetes that changes the limb image by disorders in feelings of pain and misguided valid ankle–arm value rate. In possible grading systems and clinical state of limb classification, not all of the crucial elements are included, even though they are significant in the therapy of diseased patients who suffer from critical ischaemia and diabetes. The WIfI classification includes the evaluation of three crucial elements, which are: the presence/state of the sore advancement, the presence/state of the ischaemia advancement, and the presence/state of the infection advancement.